HIV‐associated neurocognitive disorder: An investigation using structural neuroimaging in a c‐ART treated Tanzanian cohort. (31st December 2021) - McDonald, Lucy; Koipapi, Sengua; Howlett, William; Dekker, Marieke; Urasa, Sarah; Kalaria, Rajesh; Walker, Richard; Firbank, Michael J; Paddick, Stella‐Maria
Abstract: Background: There is a newly emergent ageing population of people living with HIV (PLWH) in Africa. However, there is little research into HIV‐associated neurocognitive disorder (HAND) in this population. Existing research suggests HAND is prevalent however the aetiology remains unclear. This study aims to determine whether HAND is truly prevalent and explore potential causes in PLWH on c‐ART using objective structural measures. Method: A systematic sample of PLWH aged ≥ 50 receiving combination antiretroviral treatment (cART) according to local guidelines were recruited from a HIV clinic in Kilimanjaro, Tanzania. Demographic data and comorbidities were self‐reported. HIV‐disease management data were obtained from detailed clinic data sheets. HIV viral load and CD4 count were measured. A detailed low‐literacy neurocognitive battery, informant history for functional impairment and neurological examination were conducted and HAND diagnosis made by consensus panel using AAN criteria. Cerebral atrophy (brain and ventricle volume) and WMH were measured using quantitative analysis of 1.5T MRI. Result: This cohort (n=91, 100% on cART, 64.8% female) had well‐managed HIV (75.9% suppressed viral load, median CD4 507 cells/ul). However, 66.7% had gross atrophy on their MRI scan, and HAND had a prevalence of 63.7%. The significant independent predictor (IP) of decreased brain volume was older age at HIV diagnosis (p=.001), and of increased ventricle volume was increased age (p<.0001), male gender (p<.0001) and increased frailty (p<.0001). The significant IPs of increased WMH volume were increased age (p<.0001) and smoking (p=.021). Only memory impairment independently predicted all structural measures. Conclusion: This is the first MRI study of older c‐ART treated PLWH in Africa. Despite c‐ART and good disease management, HAND was objectively prevalent and unrelated to measures of HIV disease severity. Cerebral atrophy and WMH were associated with factors of neurodegeneration. Cerebral atrophy was associated with male gender and older age at diagnosis. Association with older age at diagnosis may be 'legacy effect' of early CNS effect of the HIV virus rather than current management.